A thermal analysis study of dithizone and dithizonates of mercury, silver and bismuth - Chahud, Marisa; Carvalho Filho, Marco Aurélio da Silva; Fernandes, Nedja Suely; Ionashiro, Massao (Eclética Química, 2000)
Solid dithizonates of Hg(I), Ag(I) and Bi(III) have been prepared. Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), X ray diffraction powder patterns and elemental analysis have been used to characterize and to study the thermal stability and thermal decomposition of the dithizone and of these dithizonates.